The Hole is the Untrue. The Art of Spinning a Broken Record - Mowitt, John (Revue musicale OICRM)

(untitled) (Observatoire interdisciplinaire de création et recherche en musique (OICRM), 2023)
This is a theoretically driven consideration of the relation between art and the vinyl record that foregrounds the motif of “destruction” in attempting to comprehend this relation. Christian Marclay’s well-known work, Record Without a Cover—designed to be destroyed by individual consumers—serves as the touchstone for a series of reflections on how the aesthetic medium of the cinema has staged the destruction of records (Richard Brook’s Blackboard Jungle), or how sculptures can be fashioned from destroyed records (Jean Shin’s Sound Wave). In all cases, what resists destruction is the spindle hole, a hole that in Marclay’s recent works is given sonic resonance in “the scream” issuing from the mouth, a hole in the face. Drawing on Jacques Lacan’s discussion of “the hole” in psychosis, the essay considers how Marclay’s work operates less as a presentation of aesthetic truth, and more as an aesthetic probing of the politics of art, that is, the ability of aesthetic practice to pose questions about the ideology of an institutionally sanctioned principle of the shiny semblance (schöne Schein). Theodor Adorno’s inversion of Hegel’s “The Whole is the True,” is thus inverted—reversed and destroyed—in turn.